Impact of grow lights on crop performance under simulated growing environment - ABEENA M. A MAMATHA PRABHAKAR SIBIN C. BABY; Dr. Abdul Hakkim V. M (Guide) (Tavanur 2016 Department of Land & Water Resources and Conservation Engineering)
Impact of grow lights on crop performance under simulated growing environment
Impact of grow lights on crop performance under simulated growing environment